Lycorine and homolycorine derivatives for chemo-sensitizing resistant human ovarian adenocarcinoma cells - Sancha, Shirley A R; Dobiasová, Simona; Nejedlý, Tomáš; Strnad, Ondřej; Viktorová, Jitka; Ferreira, Maria-José U (Phytomedicine, 2024)
BACKGROUND: Multidrug resistance is the major obstacle to cancer chemotherapy. Modulation of P-glycoprotein and drug combination approaches have been considered important strategies to overcome drug resistance. PURPOSE: Aiming at generating a small library of Amaryllidaceae-type alkaloids to overcome drug resistance, two major alkaloids, isolated from Pancratium maritimum, lycorine (1), and 2α-10bα-dihydroxy-9-O-demethylhomolycorine (2), were derivatized, giving rise to nineteen derivatives (3 - 21). METHODS: The main chemical transformation of lycorine resulted from the cleavage of ring E of the diacetylated lycorine derivative (3) to obtain compounds that have carbamate and amine functions (5 - 16), while acylation of compound 2 provided derivatives 17 - 21. Compounds 1 - 21 were evaluated for their effects on cytotoxicity, and drug resistance reversal, using resistant human ovarian carcinoma cells (HOC/ADR), overexpressing P-glycoprotein (P-gp/ABCB1), as model. RESULTS: Excluding lycorine (1) (IC50 values of 1.2- 2.5 μM), the compounds were not cytotoxic or showed moderate/weak cytotoxicity. Chemo-sensitization assays were performed by studying the in vitro interaction between the compounds and the anticancer drug doxorubicin. Most of the compounds have shown synergistic interactions with doxorubicin. Compounds 5, 6, 9 - 14, bearing both carbamate and aromatic amine moieties, were found to have the highest sensitization rate, reducing the dose of doxorubicin 5-35 times, highlighting their potential to reverse drug resistance in combination chemotherapy. Selected compounds (4 - 6, 9 - 14, and 21), able of re-sensitizing resistant cancer cells, were further evaluated as P-gp inhibitors. Compound 11, which has a para‐methoxy-N-methylbenzylamine moiety, was the strongest inhibitor. In the ATPase assay, compounds 9-11 and 13 behaved as verapamil, suggesting competitive inhibition of P-gp. At the same time, none of these compounds affected P-gp expression at the mRNA or protein level. CONCLUSIONS: This study provided evidence of the potential of Amaryllidaceae alkaloids as lead candidates for the development of MDR reversal agents.
Keywords: Alkaloids; P-glykoproteiny; fenantridiny; nádorové buněčné linie; protinádorové látky; lidé; Drug Resistance, Neoplasm; Doxorubicin; ATP Binding Cassette Transporter, Subfamily B, Member 1; Antineoplastic Agents; chemorezistence; Phenanthridines; Adenocarcinoma; adenokarcinom; ATP Binding Cassette Transporter, Subfamily B; alkaloidy; Carbamates; alkaloidy amarylkovitých; Amaryllidaceae Alkaloids; karbamáty; Humans; P-glykoprotein; Cell Line, Tumor; doxorubicin